Fe-Based metal–organic frameworks as functional materials for battery applications. Issue 5 (8th February 2022) - Yang, Qingyun; Liu, Yanjin; Ou, Hong; Li, Xueyi; Lin, Xiaoming; Zeb, Akif; Hu, Lei
Abstract : This review presents a comprehensive discussion on the development and application of pristine Fe-MOFs in lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, metal–air batteries and lithium–sulfur batteries. Abstract : Metal–organic frameworks (MOFs), as a kind of organic–inorganic porous material with a high surface area, high porosity and versatile functionalities, have attracted significant research interest in the field of batteries in recent years. Among many MOF materials, Fe-based MOFs have many advantages, such as low toxicity, low cost, diverse structure types and preferable stability, which have splendid potential in practical applications. To further understand the contribution of Fe-based MOFs in battery application, we mainly review the applications of pristine Fe-MOFs in lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, metal–air batteries and lithium–sulfur batteries in detail. Their electrochemical properties as cathodes, anodes and electrocatalysts are discussed and compared from the aspects of synthesis methods, reaction conditions and additives, which is expected to provide beneficial information and new perspectives for the application of Fe-MOFs as battery materials towards high electrochemical performance. Finally, through careful reflection on the research progress, we summarize the existing problems of Fe-MOFs and provide an outlook.